Tradycja jako przekazywanie Bożego Objawienia w świetle dokumentu Międzynarodowej Komisji Teologicznej "Teologia dzisiaj: perspektywy, zasady, kryteria" - Rossa, Piotr (Włocławskie Wydawnictwo Diecezjalne, 2013)
The author of the article reflects upon of the theme of handing down Revela-tion in light of International Theological Commission’s document, Theology Today: Perspectives, Principles and Criteria. The starting point in this handing-down process is a broadly-understood listening to the Word of God. Recognizing, in light of the Word, the revealed God in Jesus Christ, one sees the whole process which has taken place through Christ’s commission to the Apostles, that they proclaim the Gospel which has been announced and fulfilled by Him. The handing down process takes place through the words and life of the Apostles; it is committed to writing, and Scripture as well as Tradition are tightly bound in order for Revelation to be handed down. This process takes place in the Church by the power of the Holy Spirit. At the same time, the Church Magisterium – which is the College of Bishops who are the Apostles’ successors by the power of succession in union with the Pope as the head – authentically interprets the deposit of faith. In this handing down process, the mission of theologians is not only individual, but collegial as well.
Tradition as the handing down of Divine Revelation in light of the Dokument of the International Theolohical Commission, Theology today: perspectives, principles and criteria
Keywords: Tradycja; Międzynarodowa Komisja Teologiczna; Objawienie Boże; Kościół; Pismo Święte; Urząd Nauczycielski Kościoła; Jezus Chrystus; tradycje